Civil liability on the field of discrimination in Chile - Pardo, Francisco Javier Talep; Nascimento, Grasiele Augusta Ferreira [UNESP] (My University, 2018)
The issue of discrimination is universal. Since man formed communities, those have been identified by their language, religion, culture, or physical appearance, etc., and in these circumstances they were also distinguished from communities that did not have those attributes. At the same time, as society grew tighter, so did the acceptance of outsiders. Chile has not escaped this trend of thought and has experienced a slower progress towards the goal of non-discrimination, particularly, if compared to Brazil and Argentina, South American countries that have advanced legal regulations about the issue. The present paper aims to present more about the subject of discrimination and its legal outreach in the area of civil law, from a historical, normative, and case law perspective.
Responsabilidad civil en materia de discriminación en Chile
Keywords: Civil Liability; Discrimination; Equality; Private Autonomy